Novel parallel combinatory system with high compaction multicarrier modulation - HOU Ya-fei1; HAMAMURA Masanori2; ZHANG Shi-yong1 (Tongxin xuebao)
A novel system named parallel combinatory/high compaction multi-carrier modulation（PC/HC-MCM） system was proposed based on techniques of high compaction multi-carrier modulation（HC-MCM） and parallel combinatory OFDM（PC-OFDM）.Compared with PC-OFDM,PC/HC-MCM can dramatically improve the bandwidth efficiency of PC-OFDM system.On the other hand,it simulated the performance of two different PC/HC-MCM systems which can be developed to apply in multi-carrier systems.